Human box C/D snoRNA processing conservation across multiple cell types - Scott, Michelle S. (Oxford University Press, 2012)
Small nucleolar RNAs (snoRNAs) function mainly as guides for the post-transcriptional modification of ribosomal RNAs (rRNAs). In recent years, several studies have identified a wealth of small fragments (<35 nt) derived from snoRNAs (termed sdRNAs) that stably accumulate in the cell, some of which may regulate splicing or translation. A comparison of human small RNA deep sequencing data sets reveals that box C/D sdRNA accumulation patterns are conserved across multiple cell types although the ratio of the abundance of different sdRNAs from a given snoRNA varies. sdRNA profiles of many snoRNAs are specific and resemble the cleavage profiles of miRNAs. Many do not show characteristics of general RNA degradation, as seen for the accumulation of small fragments derived from snRNA or rRNA. While 53% of the sdRNAs contain an snoRNA box C motif and boxes D and D′ are also common in sdRNAs (54%), relatively few (12%) contain a full snoRNA guide region. One box C/D snoRNA, HBII-180C, was analysed in greater detail, revealing the presence of C′ box-containing sdRNAs complementary to several pre-messenger RNAs (pre-mRNAs) including FGFR3. Functional analyses demonstrated that this region of HBII-180C can influence the alternative splicing of FGFR3 pre-mRNA, supporting a role for some snoRNAs in the regulation of splicing.